Influence of antiplatelet medication and anticoagulation therapy after dental extractions on hospitalization: a retrospective 10-year study - Marie Sophie Katz; Rajae Benidamou; Mark Ooms; Marius Heitzer; Anna Bock; Dirk Elvers; Timm Steiner; Florian Peters; Frank Hölzle; Ali Modabber (BMC Oral Health, 2024)
Abstract Background The aim of this retrospective study was to identify high-risk dental extraction patients and the timing of postoperative hemorrhage to evaluate whether preventive hospitalization should be considered in patients on antiplatelet medication (AP) or anticoagulants. Methods Our study included 1595 procedures; 1319 were conducted under monotherapy (Group I: AP; Group II: indirect oral anticoagulant [IAC]; Group III: direct oral anticoagulant [DOAC]) and 276 under dual therapy (Group IV: double AP; Group V: AP and IAC; Group VI: AP and DOAC). We evaluated the incidence, frequency and timing of hemorrhage, hospitalization rate, and treatment of bleeding incidents. Results The incidence of hemorrhagic events was significantly higher in the dual therapy groups compared to the monotherapy groups (p < 0.001). Comparing the procedures under monotherapy, those on DOAC (Group III) had a significantly higher risk of postoperative bleeding than Groups I and II (p < 0.001) and a higher rate of repeated bleeding episodes (p = 0.035). Regarding bleeding incidents, 44% (dual therapy) vs. 51.1% (monotherapy) occurred on the day of surgery. Conclusions The bleeding risk after dental extractions is overall low and patients were often hospitalized preventively due to their comorbidities rather than actual bleeding risk. Patients should be instructed about local compression, and surgeries should be completed in the morning to avoid emergency visits. However, patients with cardiovascular diseases and dual therapy had a higher risk of postoperative hemorrhage. Thus, hospitalization is to be considered in these cases. Trial registration The study was approved by the Ethics Committee of the Medical Faculty of RWTH Aachen (Decision Number 24-136). This was a retrospective clinical study designed to analyze postoperative bleeding and hospitalization rates after dental extractions in patients on AP or anticoagulation therapy.